Методичний підхід до формування інноваційної моделі управління персоналом будівельних підприємств на основі системи грейдів - Шевченко, В. С. (НТУ "ХПІ", 2014)
Одним із інноваційних методів мотивації персоналу є визначення цінності посад. При цьому відбувається процес оцінки та ранжування посад відносно їх впливу на кінцевий результат діяльності підприємства. Одним з інструментів, який дозволяє виявити коефіцієнт ефективності штатних одиниць є система грейдів У статті запропоновано методику впровадження системи грейдів як інноваційного методу мотивації персоналу, що спрямований на позитивну мотивацію до високоефективної та доцільної праці персоналу будівельних підприємств.

The issue of improvement of motivational systems has become urgent due to the aggravation of the situation in the field of training and competence of staff, because of the innovative activities of construction enterprises put forward new requirements to the managers of the enterprises in terms of the organization of a qualitatively new system of personnel management, aimed at strengthening the immediate interest of the workers in the results of their work. One of the innovative methods of personnel motivation is to determine the value of jobs. When this happens the process of evaluating and ranking positions with regard to their influence on the final result of the activity of the enterprise. One of the tools that allows you to identify the coefficient of efficiency units is a system of grades. In article the technique of introducing a system of grades as an innovative method of motivating staff, aimed at positive motivation for highly efficient and expedient work of the staff of construction companies.
A methodical approach to forming innovative personnel management of construction enterprises on the basis of grades system
Keywords: управління персоналом; будівельне підприємство; персонал підприємства; мотивація персоналу; грейди; personnel; bonuses; grades